Towards Inclusive Education in Cambodia: Overcoming Barriers and Embracing Diversity - Iem Chantou (Journal of Education Review Provision, 2021)
This paper examines the progress and challenges of inclusive education in Cambodia. Inclusive education aims to provide equal opportunities for all students, including those with disabilities, to access quality education. Despite some progress, inclusive education in Cambodia is still facing significant barriers, including inadequate infrastructure, limited policies, and negative attitudes towards students with disabilities. The study utilized a literature review approach to examine relevant studies and reports on inclusive education in Cambodia. The results indicate that there is a need for more investment in inclusive education, including teacher training, policy development, and infrastructure improvement. A change in societal attitudes towards disability is also required to create a more inclusive and accepting culture in Cambodia. The study recommends that the Cambodian government, in partnership with international organizations and stakeholders, take concrete steps towards achieving inclusive education and promoting equal opportunities for all students.